DRIVERS OF DIGITAL TRANSFORMATION IN REGIONAL HOSPITALS: TECHNOLOGICAL CAPABILITY, DIGITAL LEADERSHIP, AND ORGANIZATIONAL LEARNING - Nur Indayani; Almansyah Rundu Wonua; Hendrik Hendrik (Jurnal Interprof, 2026)
Purpose: To analyze the influence of technological capabilities   and digital leadership on the success of digital transformation and to examine the role of organizational learning as a moderating variable in regional hospitals Research Methodology: This study was conducted at the Benyamin Guluh Kolaka Hospital  in Southeast Sulawesi, using a quantitative approach. Data were collected via a questionnaire and analyzed using PLS-SEM. Results: Technological capabilities and digital leadership have a positive and significant impact on the success of digital transformation. In addition, organizational learning was found to strengthen the relationship between technological capabilities and digital leadership and the success of digital transformation. These findings indicate that technological readiness, leadership roles, and the organization’s ability to learn and adapt are key factors in supporting the success of digital transformation in the healthcare sector. Conclusions: Technological capabilities and digital leadership play a crucial role in enhancing the success of digital transformation at the Benyamin Guluh Kolaka Hospital (BLUD). Furthermore, organizational learning has been shown to strengthen the impact of both by enhancing the organization’s knowledge, adaptability, and readiness to face digital change. Limitations: Given that the scope of this study was limited to a regional hospital with a small number of respondents, the results cannot yet be widely generalized. Contributions: This study makes a theoretical contribution to the development of research on digital transformation, particularly in regional hospitals, by incorporating organizational learning as a moderating variable. In practical terms, the study’s findings can serve as a reference for hospital management and public sector organizations in enhancing the success of digital transformation through the strengthening of technological capabilities, digital leadership, and organizational learning.